The Apple experience secrets to building insanely great customer loyalty - Gallo, Carmine (McGraw-Hill, 2012)
Explains what makes the Apple retail experience so successful. This title details the principles and practices behind this total commitment to the customer and explains how your brand can achieve outstanding results by delivering this same high standard of service.